Global warming is dead, long live global heating? - Hulme, Mike; Nerlich, Brigitte; Pearce, Warren (University of Nottingham, 2014)
We discuss how global heating is used in comparison to global warming, look at its semantic history and examine the communicative problems it may pose and the confusion it may lead to.